Disorders of Thrombosis and Hemostasis in Pregnancy A Guide to Management - Cohen, Hannah; O'Brien, Patrick; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
Disorders of Thrombosis and Hemostasis In Pregnancy: A guide to management is a comprehensive guide to disorders of thrombosis and hemostasis in pregnancy. It highlights the latest developments and controversial issues, and the multidisciplinary approach provides authoritative clinical advice on state-of-the-art management. The disorders covered are highly pertinent to successful pregnancy outcome, and many may be associated with significant maternal and/or fetal morbidity, and even mortality. This book is relevant for individuals in all disciplines involved in the care of women with disorders of thrombosis and hemostasis in pregnancy.
HAEMOSTATIC CHANGES IN NORMAL PREGNANCY -- SYSTEMIC THROMBOEMBOLISM IN PREGNANCY: Heritable and acquired thrombophilias -- SYSTEMIC THROMBOEMBOLISM IN PREGNANCY: Thromboprophylaxis -- SYSTEMIC THROMBOEMBOLISM IN PREGNANCY: Venous thromboembolism -- PREGNANCY MORBIDITY ASSOCIATED WITH HEREDITARY AND ACQUIRED THROMBOPHILIAS:Recurrent miscarriage -- PREGNANCY MORBIDITY ASSOCIATED WITH HEREDITARY AND ACQUIRED THROMBOPHILIAS: Late obstetric complications -- ANTITHROMBOTIC THERAPY FOR CARDIAC DISORDERS IN PREGNANCY -- INHERITED AND ACQUIRED BLEEDING DISORDERS IN PREGNANCY: von Willebrand disease, factor XI deficiency, Haemophilia A and B carriers -- INHERITED AND ACQUIRED BLEEDING DISORDERS IN PREGNANCY: Rare coagulation factor defects -- INHERITED AND ACQUIRED BLEEDING DISORDERS IN PREGNANCY: Platelet defects -- THROMBOCYTOPENIA IN PREGNANCY: Gestational thrombocytopenia and Idiopathic thrombocytopenic purpura -- THROMBOCYTOPENIA IN PREGNANCY: Fetal and neonatal alloimmune thrombocytopenia -- MANAGEMENT AND OUTCOME OF PREGNANCY IN PATIENTS WITH MYELOPROLIFERATIVE NEOPLASMS -- RED CELL DISORDERS AND HAEMOGLOBINOPATHIES IN PREGNANCY -- The NEONATE -- THROMBOTIC AND HAEMOSTATIC ASPECTS OF ASSISTED CONCEPTION.
Keywords: Hematology; Obstetrics; Reproductive medicine; Blood transfusion; Internal medicine; Hematology; Obstetrics/Perinatology/Midwifery.; Reproductive Medicine; Blood Transfusion Medicine; Internal Medicine